Appendix to The Emerging Role of Data Scientists on Software Development Teams - Kim, Miryung; Zimmermann, Tom; DeLIne, Robert; Begel, Andrew (Microsoft Research, 2016)
This technical report contains supplemental materials (hierarchical taxonomy of codes, selected quotes) to the paper "The Emerging Role of Data Scientists on Software Development Teams" published at ICSE 2016.